Solubility and dissolution enhancement of HPMC ‑ based solid dispersions of carbamazepine by hot‑melt extrusion technique (Asian Journal of Pharmaceutics (AJP), 2014)
The objective of this study was to investigate solid dispersions (SDs) of poorly water soluble drug carbamazepine (CBZ),prepared using low viscosity grade hydroxypropyl methyl cellulose (HPMC) (Methocel® E3 LV and Methocel® E5 LV)by hot‑melt extrusion (HME) technology. Saturation solubility and dissolution profile of CBZ was studied. Characterizationof hot‑melt extruded samples was done by Fourier transform infrared spectroscopy (FTIR), differential scanningcalorimetry (DSC), and X‑ray diffraction studies (XRD). The result of the study showed the conversion of crystalline formof drug into amorphous form indicating increase in saturation solubility and dissolution rate of CBZ.Key words: Carbamazepine, hot‑melt extrusion, hydroxypropyl methyl cellulose